Structural Modifications of Bacterial Lipopolysaccharide that Facilitate Gram-Negative Bacteria Evasion of Host Innate Immunity - Matsuura, Motohiro (Frontiers in Immunology, 2013)
Bacterial lipopolysaccharide (LPS), a cell wall component characteristic of Gram-negative bacteria, is a representative pathogen-associated molecular pattern that allows mammalian cells to recognize bacterial invasion and trigger innate immune responses. The polysaccharide moiety of LPS primary plays protective roles for bacteria such as prevention from complement attacks or camouflage with common host carbohydrate residues. The lipid moiety, termed lipid A, is recognized by the Toll-like receptor 4 (TLR4)/MD-2 complex, which transduces signals for activation of host innate immunity. The basic structure of lipid A is a glucosamine disaccharide substituted by phosphate groups and acyl groups. Lipid A with 6 acyl groups (hexa-acylated form) has been indicated to be a strong stimulator of the TLR4/MD-2 complex. This type of lipid A is conserved among a wide variety of Gram-negative bacteria, and those bacteria are easily recognized by host cells for activation of defensive innate immune responses. Modifications of the lipid A structure to less-acylated forms have been observed in some bacterial species, and those forms are poor stimulators of the TLR4/MD-2 complex. Such modifications are thought to facilitate bacterial evasion of host innate immunity, thereby enhancing pathogenicity. This hypothesis is supported by studies of Yersinia pestis LPS, which contains hexa-acylated lipid A when the bacterium grows at 27ºC (the temperature of the vector flea), and shifts to contain less-acylated forms when grown at the human body temperature of 37ºC. This alteration of lipid A forms following transmission of Y. pestis from fleas to humans contributes predominantly to the virulence of this bacterium over other virulence factors. A similar role for less-acylated lipid A forms has been indicated in some other bacterial species, such as Francisella tularensis, Helicobacter pylori, and Porphyromonas gingivalis, and further studies to explore this concept are expected.